Transcriptomic Features in a Single Extracellular Vesicle via Single‐Cell RNA Sequencing (Small Methods 11/2022). Issue 11 (17th November 2022) - Luo, Tao; Chen, Si‐Yi; Qiu, Zhi‐Xin; Miao, Ya‐Ru; Ding, Yue; Pan, Xiang‐Yu; Li, Yirong; Lei, Qian; Guo, An‐Yuan
Abstract : Front Cover In article number 2200881, Lei, Guo, and co‐workers modified the experimental and analytical methods of single cell sequencing to single extracellular vesicle, then characterized the high‐throughput transcriptome at the single extracellular vesicle level for the first time.